A new family of distributions with properties, regression models and applications. Issue 1 (2nd January 2018) - Yousof, Haitham M.; Altun, Emrah; Ramires, Thiago G.; Alizadeh, Morad; Rasekhi, Mahdi
Abstract: In this study, we introduce a new family of continuous distributions with one extra shape parameter, called the Burr-Hatke-G family, based on the Burr-Hatke differential equation. Some of its mathematical properties are derived. The maximum likelihood method is used to estimate the model parameters. Moreover, the log-Burr-Hatke-Weibull regression model based on new the generated family is introduced. The usefulness of the proposed family is demonstrated by means of the three real data applications. Empirical results indicate that the proposed family provides more realistic fits than other well-known family of distributions.